A motivated information processing perspective on the antecedents of empowering leadership. Issue 2 (16th October 2020) - van Knippenberg, Daan; Giessner, Steffen R.; Sleebos, Ed; van Ginkel, Wendy P.
Abstract: Empowering leadership is an important influence on team effectiveness. This makes the question of what the antecedents of team empowering leadership are an important issue to consider. To address this question, we propose a motivated information processing perspective that holds that engaging in empowering leadership is based on social information processing, and that there are individual differences in how elaborate that information processing is. We argue that a key consideration in shifting control from the leader to the team is the extent to which empowering leadership is driven by leaders' consideration of their trust in the team (i.e., an instance of social information processing), and that leader need for closure (a trait capturing the disposition to carefully consider decisions and actions) moderates the relationship between leader trust in team and empowering leadership. A survey of N = 156 work teams supported these hypotheses.